Evaluation of the clinical performance of anti-mutated citrullinated vimentin antibody and 14-3-3 eta testing in rheumatoid arthritis - Nelson, Heather A.; Martins, Thomas B.; Saadalla, Abdulrahman; Nandakumar, Vijayalakshmi (Clinical chemistry and laboratory medicine, 2025)
Early rheumatoid arthritis (RA) detection is crucial for improving patient prognosis. Anticyclic citrullinated peptide antibodies (anti-CCP) and rheumatoid factors (RF) support RA diagnosis but are undetectable in ∼20 % of cases. Recently, antibodies against mutated citrullinated vimentin (anti-MCV) and detection of 14-3-3 eta have emerged with implications for preclinical RA diagnosis and monitoring treatment. The objective of this study was to assess the clinical performance of anti-MCV antibodies and 14-3-3 eta in RA and to compare it to current RA criteria anti-CCP and RF markers, individually and in combination. A retrospective chart review of 326 subjects submitted for RA serology testing identified 134 RA positive and 192 RA negative disease control individuals. Fifty healthy controls specimens were also included. Performance of anti-MCV and 14-3-3 eta, alone and combined with CCP3.1 and RF, was assessed. Anti-MCV had a sensitivity of 71 % and a specificity of 92 %. 14-3-3 eta had a sensitivity of 43 % and a specificity of 90 %. In comparison, CCP3.1 and RF displayed a sensitivity of 79 % and 84 % and a specificity of 92 % and 61 %, respectively. ROC curve analysis demonstrated CCP3.1 and anti-MCV had superior diagnostic performance compared to RF and 14-3-3 eta. In our cohort, anti-MCV and 14-3-3 eta failed to identify seronegative RA patients. Different combinations of double antibody positivity increased specificity at the cost of lost sensitivity. Individually, 14-3-3 eta, anti-MCV and CCP3.1 assays had ≥90 % specificity in diagnosed RA patients, with better sensitivities for anti-MCV and CCP3.1 than 14-3-3 eta. Overall diagnostic performance of anti-MCV was similar to CCP3.1 and RF, all of which outperformed 14-3-3 eta in our cohort.